Bullying victimization, mental disorders, suicidality and self-harm among Australian high schoolchildren: Evidence from nationwide data. (October 2020) - Islam, Md. Irteja; Khanam, Rasheda; Kabir, Enamul
Highlights: Bullying (traditional/cyber/both) increases the likelihood of depressive disorder Traditional bullying increases the odds of conduct disorder Bullying (traditional/cyber/both) increases the likelihood of suicidality All forms bullying increase the probability of self-harm Abstract: The effects of bullying on mental health among adolescents are of major public health concern, especially following modern bullying methods that technologically victimize adolescents. However, the independent effects of different forms of bullying (traditional, cyberbullying or both) on different types of mental disorders, suicidality and self-harm are not clear. Using a cross-sectional study design, involving 2166 Australian high schoolchildren (1131 Boys and 1035 Girls) aged 12-17 years, this study examined the associations of bullying victimization (traditional, cyber and both) with mental disorders, suicidality (ideation, plan and attempt) and self-harm. Both bivariate and multivariate analyses were employed to assess the associations. Victims of traditional bullying and cyberbullying incurred a significantly higher risk of major depressive disorder, suicidality and self-harm compared to those who had not encountered such threats. Findings also indicated the need for early identification of bullying victims to prevent the risk of mental disorders, suicidality and self-harm in schoolchildren. Furthermore, this evidence can be utilized to inform decisions regarding the provision of resources to address this important health issue in the context of any developed countries like Australia.